Local political outcomes impact of dynasties to the health and education sector - Torrecampo, Christinne Jeremiah B. (School of Economics, University of the Philippines Diliman, 2018)
With the trend towards decentralization of Local Government Units (LGUs) and the resulting control of local politics in shaping policies, budget allocations, and programs, we aim to investigate whether political dynasties could significantly impact aggregated health and education outcomes. We investigate the Health and Education sectors due to the varying degrees of decentralization in the two departments. We employ a two-term (2010 and 2013) provincial data from the Asian Institute of Management (AIM) dataset, enrolment statistics from the Department of Education, and Field Health Services Information System (FHSIS) database from the Department of Health as the primary variables used in the study. We find that there is no robust effect of dynasties on education. In contrast, we find that there is a robust and statistically significant positive relationship between the dynastic share and health-related infrastructures. Such results might be indicative of the varying degrees of decentralization between the two sectors of the government.